Measuring non-commercial tourism traffic in Croatia: Challenges of using administrative data - Zrinka Marušić; Marijana Kožul; Ivana Brozović (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2020)
National statistical authorities are under pressure to provide reliable and readily accessible data with minimum costs and respondent burden. To this end, a use of administrative data, defined as those not primarily collected for statistical purposes, is increasingly encouraged to supplement sample and census surveys. In this paper, a possibility to produce new statistics by combining several sources where at least one is the administrative data is tested. This exercise was applied to measure a volume of tourists (residents and non-residents) staying in non-commercial accommodation facilities in Croatia. Four data sources were analysed: (i) administrative data from eVisitor system, a unique online central information system for tourists registration in Croatia that provides insights into tourist traffic and accommodation capacities (commercial and non-commercial), (ii) Croatian Bureau of Statistics Survey on Tourist Activity of the Croatian population, that provides information on number of domestic trips and nights in commercial and noncommercial accommodation establishments, (iii) Croatian National Bank Survey on foreign visitors in Croatia, that estimates number of foreign tourist nights in Croatia in, both, commercial and non-commercial type of accommodation, and (iv) administrative data from Tax Register on paid taxes on second homes - holiday houses and apartments. The results clearly demonstrated that two survey-based data sources and the administrative one regarding the second homes taxes had not provided a quality foundation to improve the current estimations of tourist traffic in non-commercial accommodation provided by the eVisitor system.
Keywords: Z30; Z38; Z39; 330; administrative data sources; non-commercial accommodation; tourism statistics; tourists' overnights